1974
DOI: 10.1677/joe.0.0630021
|View full text |Cite
|
Sign up to set email alerts
|

Serial Assays of Plasma Growth Hormone in Treated and Untreated Acromegaly

Abstract: SUMMARY Assays for human growth hormone (HGH) were carried out on 89 acromegalic patients, 81 of whom were studied before any treatment had been given. Serial studies were undertaken, generally at 6-monthly intervals, with the same test procedure, using a 50 g oral glucose tolerance test (GTT) and identical assay conditions over a period of 8 years. Twenty-three patients were assessed at intervals during periods of up to 4 years whilst they remained untreated. The general picture was one of unchanging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1974
1974
1986
1986

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The reported bioassayable GH values by the tibia test method in rats (Contopoulos & Simpson 1957;Dickermann et al 1969) and in patients with gigantism or acromegaly (Gemzell 1959;Gemzell et al 1955;Segaloff et al 1955) are in excess of those measured bv radioimmunoassav (Hunter et al 1974;Schalch & Reichlin 1966). In addition, Ellis & Grindeland (1974) with the tibia test could demonstrate bioassayable GH in the pooled plasma of normal human subjects and this bioassavable GH was found to be 200 times greater as compared to radioimmunoassavable GH.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The reported bioassayable GH values by the tibia test method in rats (Contopoulos & Simpson 1957;Dickermann et al 1969) and in patients with gigantism or acromegaly (Gemzell 1959;Gemzell et al 1955;Segaloff et al 1955) are in excess of those measured bv radioimmunoassav (Hunter et al 1974;Schalch & Reichlin 1966). In addition, Ellis & Grindeland (1974) with the tibia test could demonstrate bioassayable GH in the pooled plasma of normal human subjects and this bioassavable GH was found to be 200 times greater as compared to radioimmunoassavable GH.…”
Section: Discussionmentioning
confidence: 98%
“…Ellis & Grindeland (1974) reported a discrepancy be¬ tween biological growth activity (bioassayable GH) determined with the tibia test (Greenspan et al 1949) and the amount of radioimmunologically measurable growth hormone (radioimmunoassayable GH) in human plasma. Moreover, in patients with acromegaly several studies have demonstrated a poor correlation between radioimmunoassayable GH levels and clinical evidence of activity (Bau¬ mann et al 1983;Daughaday 1979;Herington et al 1974;Hunter et al 1974). To further study the bioassayable GH using another method, the biolog¬ ical growth activity was determined with the tetracycline bone growth test (Thorngren & Hansson 1974a,b,c) in blood from healthy blood donors and patients with acromegaly.…”
mentioning
confidence: 99%
“…Only in a few studies a subset of acromegalie patients are mentioned who have not received any treament. Hunter et al (1974) reported on longterm changes of plasma GH levels in 23 untreated acromegalie patients during periods up to 4 years, but in that study clinical activity and tumour size were not taken into account. Moreover, only 7 patients were followed for more than one year and 4 of these 7 patients for more than 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional external irradiation is widely available but it lowers growth hormone level slowly, and probably in only about half the patients does it reach normal within the first four years (Hunter et al, 1974). Other pituitary hormones are not usually affected by this form of treatment, but there is a small risk of malignant change in the region of the pituitary fossa ( Table 6 Methods of treating patients with acromegaly irradiation is not available in Britain.…”
Section: Methods Of Treatmentmentioning
confidence: 99%